Menemukan Bahasa Anak dalam Pelukan Gambar dan Kata (Studi pada Anak Berkebutuhan Khusus di PAUD Reguler) - Imelda Hutabarat (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to examine the implementation of differentiated instruction combined with flashcard media in supporting the language development of children with special needs at TK Kartika I-II Aceh Besar. A descriptive qualitative approach with a case study design was employed, involving three children diagnosed with ADHD, communication disorders, and Down syndrome, along with two classroom teachers. Data were collected through participatory observation and in-depth interviews. The findings reveal that this integrative instructional approach promoted increased participation, vocabulary acquisition, and communicative responsiveness in the children. Previously passive children began to use visual cues, repeat simple words, and showed improved focus during learning activities. The study highlights the importance of language-focused, individualized interventions in inclusive education, especially for children with special needs who are accepted in mainstream schools. It recommends the integration of differentiated instruction and concrete visual media as effective methods for enhancing equitable language learning opportunities within the implementation of the Merdeka Curriculum in inclusive early childhood education settings. Keywords: Language Development; Differentiated Instruction; Flashcards; Special Needs Education; Inclusive Learning; Early Childhood Education; Merdeka Curriculum